2020
DOI: 10.1021/acsphotonics.0c00310
|View full text |Cite
|
Sign up to set email alerts
|

Toward Bright and Pure Single Photon Emitters at 300 K Based on GaN Quantum Dots on Silicon

Abstract: Quantum dots (QDs) based on III-nitride semiconductors are promising for single photon emission at non-cryogenic temperatures due to their large exciton binding energies. Here, we demonstrate GaN QD single photon emitters operating at 300 K with g (2) (0) = 0.17±0.08 under continuous wave excitation. At this temperature, single photon emission rates up to 6 × 10 6 s −1 are reached while g (2) (0) ≤ 0.5 is maintained. Our results are achieved for GaN QDs embedded in a planar AlN layer grown on silicon, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 63 publications
2
52
0
Order By: Relevance
“…However, a reliable SPE platform with a high signal to noise ratio and relatively low g (2) (0) must be achieved by the growth of high-quality material with a higher emission energy of ~3 eV. Due to the large exciton binding energies of III-nitride semiconductor quantum dots (QDs), they are promising candidates for single-photon emission at noncryogenic temperatures [52].…”
Section: Quantum Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a reliable SPE platform with a high signal to noise ratio and relatively low g (2) (0) must be achieved by the growth of high-quality material with a higher emission energy of ~3 eV. Due to the large exciton binding energies of III-nitride semiconductor quantum dots (QDs), they are promising candidates for single-photon emission at noncryogenic temperatures [52].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…It has been reported that GaN QD single-photon emitters can operate at 300 K and their performance for the emission of single photons depends on the balance between the emission line width and the biexciton binding energy [52]. It has been shown that when using GaN QDs embedded in a planar AlN layer, grown on silicon, the brightness and single-photon purity can be adjusted to improve the performance metrics [52]. Authors have described that the large exciton binding energies lead to high brightness and, by the spectral overlap with the biexcitonic emission, this can be used to affect the single-photon purity.…”
Section: Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in wide-bandgap III-nitride semiconductors continues to progress rapidly, especially for the materials with bandgap exceeding that of gallium nitride (3.4 eV). Specifically, III-nitride based heterostructures provide new opportunities for a wide range of research and device applications, such as piezotronics and piezophototronics [1], self-powered photoelectrochemical-type photodetectors [2], room-temperature quantum emitters [3], single photon emitters [4][5][6], resonant tunneling diodes [7], highelectron-mobility transistors [8,9], efficient photoelectrocatalysts for solar water splitting [10], multi-wavelength light-emitting diodes (LEDs) [11,12], and deep ultraviolet (DUV)-LEDs [13][14][15][16][17]. AlGaN-based DUV-LEDs represent a sustainable alternative to replace the environmentally harmful conventional mercury lamps [18] and thus, are becoming crucial for many applications such as water purification and/or inactivation of microorganisms, including bacteria, fungi, and viruses [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, single-photon emission can be obtained in a wide spectral range from medium ultraviolet to the optical telecommunication C-band (1.55 m) through optical pumping of single QDs fabricated in different material systems [ 4 , 5 , 6 , 7 , 8 ]. Most of such emitters operate at cryogenic temperatures and only the epitaxial QDs made of wide-band-gap materials can work as SPE up to room temperature [ 9 , 10 ]. Alternative systems for producing single-photon emission at elevated temperatures could be single molecules [ 11 ], diamond color centers [ 12 ], and colloidal quantum dots [ 13 ].…”
Section: Introductionmentioning
confidence: 99%